2015
DOI: 10.1002/cmdc.201402562
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a MAO‐B‐Selectively Activated Prodrug Based on MPTP: A Mitochondria‐Targeting Chemotherapeutic Agent for Treatment of Human Malignant Gliomas

Abstract: Malignant gliomas, including glioblastomas, are extremely difficult to treat. The median survival for glioblastoma patients with optimal therapeutic intervention is 15 months. We developed a novel MAO-B-selectively activated prodrug, N,N-bis(2-chloroethyl)-2-(1-methyl-1,2,3,6-tetrahydropyridin-4-yl)propanamide (MP-MUS), for the treatment of gliomas based on 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). The design of neutral MP-MUS involved the use of a seeker molecule capable of binding to mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Another interesting idea is based on the high activity of one of the isoforms of monoamine oxidases (MAO), MAO-B in GBM [131]. Monoamine oxidase-B is located on the outer mitochondrial membrane, it is normally highly expressed by astrocytes and oxidizes various amines and other molecules.…”
Section: Can Differences In Glioblastoma Multiforme Mitochondria Be Umentioning
confidence: 99%
“…Another interesting idea is based on the high activity of one of the isoforms of monoamine oxidases (MAO), MAO-B in GBM [131]. Monoamine oxidase-B is located on the outer mitochondrial membrane, it is normally highly expressed by astrocytes and oxidizes various amines and other molecules.…”
Section: Can Differences In Glioblastoma Multiforme Mitochondria Be Umentioning
confidence: 99%
“…Lifespan was prolonged [9][10][11][12], the cognitive function [13] and sexual activity of rats were definitely improved by chronic treatments of selegiline, which were reported in a number of in vivo studies [14][15][16]. Nowadays, these effects are summarized as senolytic [17]. According to Kitani et al [9] the lifespan-prolongating effect of selegiline can be explained by its upregulating effect in the dopaminergic brain areas of several animal species (mice, rats, hamsters and dogs) on the activity of anti-oxidant enzymes such as catalase (CAT) and superoxide dismutase (SOD).…”
Section: Introductionmentioning
confidence: 99%
“…A full description of the synthesis and characterization of MP-MUS has been recently published by our laboratory ( Sharpe et al, 2015 ). The synthetic route taken for the synthesis of MP-MUS that was used in our initial work is found in Supplemental Experimental Procedure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the high levels of MAOB in the mitochondria of glioma cells, MP-MUS is expected to have increased specificity for glioblastoma cells. We have recently shown that MP-MUS is a MAOB specific substrate and that the oxidized product, P + -MUS, is indeed toxic toward cultured glioblastoma cells, but not normal human astrocytes ( Sharpe et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%